The value of non-invasive ventilation. Issue 11 (25th June 2014) - Hull, Jeremy
Abstract : Non-invasive ventilation (NIV) use has increased markedly over the last 10 years. Children being treated with NIV are now a common sight in most paediatric intensive care units and high dependency units and nearly all tertiary respiratory units will look after a cohort of children who use NIV at home. Although the published evidence base for use of NIV in acute and chronic respiratory failure is relatively weak, it is now very unlikely that there will be any more randomised controlled trials of this intervention. Effectiveness of NIV will need to be evaluated on each child as it used. It is important to define the purpose of using NIV in each child, and then determine whether it is effective.